Global profiling of the proteome, phosphoproteome, and N-glycoproteome of protoscoleces and adult worms of Echinococcus granulosus - Wang, Zhengrong; Jia, Xinyue; Ma, Jing; Zhang, Yanyan; Sun, Yan; Bo, Xinwen (Frontiers in Veterinary Science, 2023)
Cystic echinococcosis (CE) is a chronic zoonosis caused by infection with the metacestode of the Echinococcus granulosus. A unique characteristic of E. granulosus protoscolex (PSC) is their ability to develop bidirectionally into an adult worm in the definitive host or a secondary hydatid cyst in the intermediate host. Furthermore, cestodes have a complex life cycle involving different developmental stages; however, the mechanisms underlying this development remain unknown. Several studies have demonstrated that certain matrix proteins undergo posttranslational modifications (PTMs), including phosphorylation and glycosylation, which have important regulatory effects on their functional properties. Systematic analyses of the proteome, phosphorylated modified proteome, and glycosylated modified proteome of protoscoleces (PSCs) and adult worms were performed using a proteomic strategy. In total, 6407 phosphorylation sites and 1757 proteins were quantified. Of these, 2032 phosphorylation sites and 770 proteins were upregulated, and 2993 phosphorylation sites and 1217 proteins were downregulated in adult worms compared to PSCs. A total of 612 N-glycosylation sites were identified in the 392 N-glycoproteins. Of these, 355 N-glycosylation sites and 212 N-glycoproteins were quantified. Of these, 90 N-glycosylation sites and 64 N-glycoproteins were upregulated, and 171 N-glycosylation sites and 126 N-glycoproteins were downregulated in adult worms compared to PSCs. GO enrichment analysis indicated that the differentially expressed phosphoproteins were mainly enriched in the regulation of oxidoreduction coenzyme metabolic processes, myelin sheath, and RNA helicase activity, whereas the differentially expressed N-glycoproteins were enriched in the cellular response to unfolded proteins, endoplasmic reticulum lumen, and nucleic acid binding. KEGG enrichment analysis indicated that the differently expressed phosphoproteins were mainly enriched in RNA transport, hypertrophic cardiomyopathy (HCM), glycolysis/gluconeogenesis, HIF-1 This is a provisional file, not the final typeset article signaling pathway and pyruvate metabolism. Differentially expressed N-glycoproteins were enriched in the PI3K-Akt signaling pathway, ECM-receptor interactions, and protein processing in the endoplasmic reticulum. To our knowledge, this study is the first global phosphoproteomic and Nglycoproteomic analysis of E. granulosus, which provides valuable information on the expression characteristics of E. granulosus and provides a new perspective to elucidate the role of protein phosphorylation and N-glycosylation in the development of E. granulosus.